Knowledge and practice of the prevention of mother-to-child transmission of HIV guidelines amongst doctors and nurses at Odi Hospital, Tshwane District - Kingsley Ogbonna; Indiran Govender; John Tumbo (South African Family Practice)
Background: Almost 60 million people are infected with and 25 million people have already died from HIV/AIDS. Sub-Saharan Africa is the region most affected, with 67% of all people living with HIV and 91% of all new infections amongst children and 14 million children orphaned by HIV-related deaths. HIV can be transmitted from a pregnant mother to her child during pregnancy, birth or breastfeeding. In South Africa (SA) the mother-to-child HIV transmission (MTCT) rate is under 4% at 4 to 8 weeks after birth since implementation of the most recent national prevention of MTCT (PMTCT) programme.